The Effectiveness of Problem-Based Learning Model on Students' Learning Independence and Mathematical Creative Thinking Abilities - Aziza Khairu Rokhis; Maximus Gorky Sembiring; Endang Wahyuningrum (CV. Creative Tugu Pena, 2025)
This study investigates the effectiveness of the Problem-Based Learning (PBL) model in fostering students’ learning independence and mathematical creative thinking skills. The research was conducted with seventh-grade students at SMP Negeri 2 Mesuji, Lampung, during the odd semester of the 2024/2025 academic year. The population comprised 216 students across seven classes, from which two classes were selected using cluster random sampling. A pretest–posttest control group design was employed. Data were collected through essay tests on the topic of social arithmetic and questionnaires assessing students’ learning independence. The data were analyzed using t-tests, N-Gain analysis, and one-proportion z-tests. The results indicate that the PBL model was more effective than conventional learning in enhancing both mathematical creative thinking and learning independence. The experimental group achieved a significantly higher average N-Gain score than the control group. Furthermore, over 60% of students in the experimental class attained a “good” category in learning independence after the intervention. Improvements in creative thinking indicators—fluency, flexibility, originality, and elaboration—were also more pronounced in the PBL group. These findings demonstrate that Problem-Based Learning not only improves students’ cognitive abilities but also cultivates essential learning dispositions such as independence and creativity. This research provides empirical support for the integration of student-centered learning models in mathematics education to promote higher-order thinking skills.